PEMBUATAN SEDIAAN SERBUK INSTAN DAUN SIRSAK (Annona muricata L.) DIKOMBINASIKAN DENGAN SARI BUAH NANAS (Ananas comosus L.) UNTUK MENCEGAH PENINGKATAN KADAR ASAM URAT - Yuliani, Suci Tri; Putra, Risa Kota; Ratnasari, Dewi (Journal of Holistic and Health Sciences (Jurnal Ilmu Holistik dan Kesehatan), 2020)
Purpose: This study aims to determine how to make instant powder formulation of soursop leaves (Annona muricata L.) combined with pineapple juice (Ananas comosus L.) which is beneficial for health. Methods: This research uses action research method. The research instruments used were observation sheets and questionnaires. The preparations were made by comparing the soursop leaf extract formulation and pineapple juice (F1, 125ml: 375ml; F2, 250ml: 250ml and F3, 375ml: 125ml) and added 200gr of sugar each. Results: The study showed that the instant powder formulation that was successfully prepared with the best results was the F3 formulation with a ratio of 375 ml of soursop leaf extract, 125 ml of nans fruit juice, and 200 g of sugar. Organoleptic observations of instant powder preparations were stable in storage for three weeks. Conclusion: The second sample F3 instant powder formulation was preferred and accepted by the public because of the better color due to the more precise heating temperature of the manufacturing process.